Self-reported and measured weight, height and body mass index for the diagnosis of the nutritional status in people living with HIV/AIDS - LIMA,Rafaela Lira Formiga Cavalcanti de (2017)
ABSTRACT Objective To validate self-reported weight and height data for people living with HIV/AIDS. Methods This cross-sectional study involved 481 people living with HIV/AIDS seen at a reference unit in João Pessoa, state of Paraíba, Brazil, between September and December 2015, 99 (20.5%) of whom had their weight and height measured. The intraclass correlation coefficient was calculated to determine the relationship between the self-reported and measured weight, height and body mass index values, and linear regression analysis was used to generate equations to predict weight and height. It were significant p-value under 5% for statistic tests applied. Results In the sample with measured values, 57.6% of men, with a mean age of 44 years old and a mean income per capita equivalent to US$145.50, high correlations (r>0.90) between the self-reported and measured values for weight, height and body mass index were observed. The accuracy was 92.6%, and the Kappa coefficient was greater than 0.85. Women tended to underestimate weight and overestimate height. The men overestimated weight and underestimated height. The intraclass correlation coefficients were greater than 0.95. Conclusion The use of self-reported measures of weight, height and body mass index for nutritional assessment of people living with HIV/AIDS is valid and must be considered for similar populations when time and resources are limiting factors.